Device Fabrication of 60 mm Resonant Cavity Light-Emitting Diode - Reyes, J. J. C.; Bisquerra, W.; Sarmago, R. V.; Salvador, A. A. (Science Diliman: A Journal of Pure and Applied Sciences; Vol 16 No 2 (2004), 2007)
An array of 60-mm-diameter resonant cavity light-emitting diodes suited for coupling with fiber optic were fabricated using standard device fabrication technique. I-V characterization was used to determine the viability of the device fabricating process. Under forward bias, the turn-on voltage of the devices is 1.95–2.45 V with a series resistance of 17–14 kW. Under reverse bias, the devices showed a breakdown voltage of 35 V.